2008
DOI: 10.1016/s0377-1237(08)80099-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Nutritional Status of School Children

Abstract: Background : A cross sectional study was carried out to determine the nutritional status of school children in Army School, Pune. Methods: Anthropometric survey of 760 school children was carried out and compared against the NCHS/WHO reference standards to determine their nutritional status. Associations of nutritional status with socio-economic status, education status of parents, mothers working status and family size were determined. Result: The prevalence of stunting was 13.81%, wasting 6.71% and under nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 7 publications
6
26
4
1
Order By: Relevance
“…In the literature the mother's education has shown stronger effect on child's nutritional status than other demographic and economic variables (Mukherjee et al, 2008). The mother's education effect has been found about twice larger than father's education in Ethiopia (Christiansen and Alderman, 2004).…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…In the literature the mother's education has shown stronger effect on child's nutritional status than other demographic and economic variables (Mukherjee et al, 2008). The mother's education effect has been found about twice larger than father's education in Ethiopia (Christiansen and Alderman, 2004).…”
Section: Literature Reviewmentioning
confidence: 96%
“…It may be due to poverty and poor knowledge of farmer mothers or paying less attention to their children because of their high work load. In India the incidence of wasting was higher for those children whose mothers were working (Mukherjee et al, 2008). However, in Nigeria mother's working status negatively affects the child health during infancy and positively in childhood, which may be due to lesser time for infants as required but enhanced family income contributed by working mother for childhood (Ukwuani and Suchindran, 2003).…”
Section: Mother's Working Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…However there was no statistically significant difference in the mean weights of the boys and girls in any of the age groups. [10] The study by Prabhakar and Gangadhar [11] showed that about 41.5% of mild stunting (based on Waterlow's classification) was recorded in all age groups and both sexes, followed by moderate stunting in 39.3%. Severe stunting was observed in 6.7% of children.…”
Section: Discussionmentioning
confidence: 99%
“…[10] These researchers did not report about the percentage of children who were overweight or obese. In a study conducted at SNDT Women's University in Mumbai, 7.7 percent of children aged 7 to 10 years were overweight and 13.2 percent were obese.…”
Section: Discussionmentioning
confidence: 99%